Amino-modification and successive electrochemical reduction of graphene oxide for highly sensitive electrochemical detection of trace Pb2+. (November 2016) - Li, Mingjie; Li, Zehui; Liu, Chenming; Chang, Yu; Wen, Jiawei; Zhao, He; Cao, Hongbin; Zhang, Yi; Liu, Dagang
Abstract: Both synthesis method and heteroatom doping could tailor graphene properties and promise its practical application. Here, a facile electrolytic route was developed to prepare amino-functionalized graphene, which could be directly used to build chemical sensor electrode. In this method, graphene oxide (GO) was electrolyzed in ethylenediamine aqueous solution to induce ammonization and electrochemical reduction successively. The unique chemical structure of ammoniated reduced GO (AErGO) strongly increased the chelation between electrode surface and Pb 2+, and provided plenty active sites for electrochemical redox. Therefore, AErGO exhibits good electrical conductivity and high electrocatalytic activities, which ensures high selectivity, low detection limit (0.0924 μg L −1 at S / N = 3) and ultra wide linear range (0.5–350 μg L −1 ) during the Pb 2+ detection. This simple and effective route can also be extended in the preparation of S-doping or S, N-dual doping graphene materials with potential applications in chemical sensor, electrochemical catalysis, and energy conversion or storage.